Voice and communication therapy with trans and non-binary people : sharing the clinical space - Mills, Matthew (Speech and language therapist); Stoneham, Gillie (Jessica Kingsley Publishers, 2021)
"Specifically aimed at Speech and Language Therapists (SLTs) and voice practitioners, this book follows up from the authors' first book, The Voice Book for Trans and Non-Binary People. It sets out a range of innovative games, activities, frameworks and exercises to helps SLTs develop their skills for working with trans clients, including emotional intelligence, role-play and solution-focused therapy. Focusing on individual therapy as well as group therapy settings, this guidebook also explores the importance of social communication games and the development of social skills for modulating or changing pitch, resonance and intonation. Written by two leading authorities on voice and communication therapy for trans people, this is an essential and authoritative resource for anyone working with trans and non-binary clients who are seeking their authentic voice"--